Poly(oligoethylene Glycol Methacrylate): A Promising Electrolyte Polymer - Imee A. Saladaga (Science Faculty of Chiang Mai University, 2019)
In this work, the polymer electrolyte based on poly(oligoethylene glycol methacrylate) was studied and found to be a promising electrolyte polymer. The polymer was synthesized using conventional free radical polymerization and characterized using Fourier transform infrared spectroscopy and thermogravimetric analysis. Ionic conductivity was measured using impedance spectroscopy as a function of polymer type, iodine/iodide concentration, additive type and concentration, and polymer blend composition. The additives used in this study were TiO2 nanoparticles, propylene carbonate, g-butyrolactone, and 1-methyl-3-propylimidazolium iodide, whereas poly(ethylene glycol) and poly(vinyl alcohol) were used to prepare the polymer blends with poly(oligoethylene glycol methacrylate). It was found that the ionic conductivity of poly(oligoethylene glycol methacrylate) was about 40 times higher than that of commonly used polymers, such as poly(ethylene glycol) and poly(vinyl alcohol). This work thus demonstrates that poly(oligoethylene glycol methacrylate) is a good candidate to be used as an electrolyte polymer for a variety of electronic applications.